2008
DOI: 10.1038/emboj.2008.231
|View full text |Cite
|
Sign up to set email alerts
|

Structural determinants of Kvβ1.3-induced channel inactivation: a hairpin modulated by PIP2

Abstract: Inactivation of voltage-gated Kv1 channels can be altered by Kvbeta subunits, which block the ion-conducting pore to induce a rapid ('N-type') inactivation. Here, we investigate the mechanisms and structural basis of Kvbeta1.3 interaction with the pore domain of Kv1.5 channels. Inactivation induced by Kvbeta1.3 was antagonized by intracellular PIP(2). Mutations of R5 or T6 in Kvbeta1.3 enhanced Kv1.5 inactivation and markedly reduced the effects of PIP(2). R5C or T6C Kvbeta1.3 also exhibited diminished binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 28 publications
1
36
4
Order By: Relevance
“…Kruse et al (2012) showed that phosphatidylinositol 4,5-bisphosphate (PI(4,5)P 2 ) depletion inhibited K v 7.1 and K v 7/2/7.3 channel current by more than 90%; in contrast to previous work (Decher et al, 2008;Oliver et al, 2004) they did not observe such PIP 2 -dependence in other members of the K v family (Kruse et al, 2012).…”
Section: Voltage-gated K + -Channelscontrasting
confidence: 47%
“…Kruse et al (2012) showed that phosphatidylinositol 4,5-bisphosphate (PI(4,5)P 2 ) depletion inhibited K v 7.1 and K v 7/2/7.3 channel current by more than 90%; in contrast to previous work (Decher et al, 2008;Oliver et al, 2004) they did not observe such PIP 2 -dependence in other members of the K v family (Kruse et al, 2012).…”
Section: Voltage-gated K + -Channelscontrasting
confidence: 47%
“…Structural studies on Kir channels (1,2,5) demonstrated that PIP 2 directly interacts with the channels. Subsequent studies supported that PIP 2 also interacts directly with voltage-gated potassium (Kv) channels (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Several positive residues that may be critical for PIP 2 activity have been identified (7,11,18,(20)(21)(22)(23)(24).…”
mentioning
confidence: 96%
“…For examples, the K V β1.3 N-terminus, unlike K V β1.1, may enter the pore as a hairpin and the inactivation conferred by this subunit and may be modified by the cellular metabolite PIP2. 28 So while some similarity in mechanism seems evident from our data and those of others, there are undoubtedly significant differences, which makes comparative studies among the K V β1 splice variants important in the future.…”
Section: Discussionmentioning
confidence: 78%
“…Ablation of the unique N-terminus eliminates the negative shift produced by K V β1.2 on K V 1.2, 24 and mutations in K V β1.3 that remove fast inactivation make the shift in K V 1.5 activation less pronounced. 28 Modeling of ionic current data suggests that open channel block by the N-terminus, in addition to causing fast inactivation, can produce saturation of activation at depolarized potentials and thus an apparent negative shift in activation. 29 Slowed channel deactivation is consistent with the inability of the channel gate to close while the K V β1 N-terminus (Fig.…”
Section: Introductionmentioning
confidence: 99%